Efektivitas Meronce Rainbow Palapah Batiak Terhadap Perkembangan Motorik Halus Di Taman Kanak-Kanak - Asha Linna, Octri; Ismet, Syahrul (Sekolah Tinggi Agama Islam Al-Kifayah Riau, 2022)
This study aims to determine the effectiveness of the meronce rainbow palapah batiak activity on fine motor development in the Pembina State Kindergarten, Pasaman District, West Pasaman Regency. The sample of this research was 30 children in groups B1 and B2 of the Public Kindergarten of Pasaman District, consisting of 15 children in the experimental class and 15 children in the control class. This study uses a quasi-experimental design with a pre-test and post-test control group. In this study the data collection techniques in the form of experiments and observations. Then test the quality of the research instrument with a validation test with professional judgment and process the results of the instrument data using SPSS version 22.0 using the Alpha Crombach technique. While testing the hypothesis using the statistical T-test technique with the help of SPSS version 22.0 which shows a significant level of 0.148. It can be concluded that the meronce rainbow palapah batik activity is effective on fine motor development in the Pembina State Kindergarten, Pasaman District, West Pasaman Regency